Integrating proteomics revealed the key targets for molecular breeding of fine cashmere traits in cashmere goats - Zhang, Chongyan; Wang, Yichuan; Xing, Anru; Xu, Bo; Wang, Mingkun; Wang, Zhixin; Liu, Zhihong (Frontiers in Veterinary Science, 2025)
In this study, the molecular mechanism of superfine fiber properties of Inner Mongolia Alpas cashmere was revealed by using fiber physical properties measurement and deep proteomics technology. The results showed that the average diameter of Alpas cashmere fiber (14.13 μm) was significantly lower than that of ordinary cashmere (17.29 μm). A total of 79 functional annotation proteins were identified by proteomics analysis, of which 28 were differentially expressed proteins (DEPs). The key findings showed that the down-regulated expression of keratins such as KRT5, KRT14, KRT8, KRT18, and keratin-associated proteins such as KRTAP11-1 and KRTAP15-1 were the core molecular nodes affecting fiber fineness. Functional enrichment analysis showed that these DEPs were significantly concentrated in biological processes such as intermediate fibrous tissue, keratinization, and epithelial cell differentiation, and were localized to keratin filaments. Further studies have found that the enrichment of the estrogen signaling pathway may indirectly affect fiber diameter by regulating the hair follicle cycle, and the interaction between serum albumin (ALB) and keratin group provides a key nutrient transport guarantee for fiber growth. PPI network analysis confirmed that KRT5, KRT14, and other proteins were at the hub of the regulatory network. Parallel reaction monitoring targeted verification ensures the reliability of proteome data. This study proposes that the down-regulation of specific keratins and their associated proteins leads to the formation of finer fibers by finely regulating the differentiation of hair follicle basal cells, cytoskeleton assembly, and keratinization. This study provides an important target for molecular breeding of cashmere goats. By targeting and improving these key genes, it is expected to cultivate new varieties with better cashmere and promote the sustainable development of the industry.